Economic Integration in the Lower Congo Region : Opening the Kinshasa-Brazzaville Bottleneck - Brulhart, Marius; Hoppe, Mombert (2012)
This working paper assesses cross-border economic integration in the Lower Congo region. It focuses on the Kinshasa-Brazzaville conurbation, which is projected to become Africa's largest urban area by 2025, and is already serving as the gateway to large hinterlands. Despite their size and proximity, formal economic exchanges between the two cities are extremely limited. The volume of recorded passenger travel between Kinshasa and Brazzaville corresponds to about one-fifth of the volume of traffic between East and West Berlin during the time of the Berlin Wall, and formal trade volumes are derisorily small. As a consequence, the authors find evidence of statistically significant differences in retail prices, indicating unexploited scope for cross-river arbitrage. Through a survey of firms, they find that local traders perceive substantial scope for increasing cross-border economic activity if cross-river trade costs were reduced. Trade in locally produced goods and by small firms would especially benefit from such reductions. Existing high trade costs mainly result from a lack of competition in cross-river transport services, which are dominated by a duopoly of state-controlled operators. High administrative border costs, exacerbated by the presence of multiple government agencies at the border, act as a further obstacle. Liberalization of cross-river transport and customs reform could yield large economic benefits for local producers and consumers.